(untitled) (Health Renaissance, 2012)
Background: Postoperative shivering is a common event of unknown etiology. Objectives: To compare the efficiency of tramadol with that of pethidine in controlling post anaesthetic shivering. Methods: This double . blind randomized clinical trial was performed on 120 consecutive patients who received general anaesthesia for elective abdominal surgery. Intravenous tramadol (1mg.kg-1) or pethidine (0.5mg.kg-1) was administered to alternate subjects who developed post anaestheic shivering. They were monitored in the recovery room for 1 hour and the cessation time of shivering, recurrence of the events, duration of recovery, respiratory depression, arterial O2 saturation, nausea and vomiting were recorded. Results: Forty-eight patients (40%) had post anaesthetic shivering. In the tramadol group, shivering terminated within 5 minutes after injection. They had no recurrence of shivering, respiratory depression, reduction in SPO2, nausea and vomiting during the period of recovery. In the pethidine group, shivering terminated within 8 minutes after injection, but in 7 patients it recurred after 30 minutes. Similarly, 6 patients had respiratory depression, reduction in SPO2 and 10 patients had nausea, vomiting but none of them needed further medication. Conclusion: Tramadol is superior to pethidine as it induces a faster termination of post anaesthetic shivering and does not entail adverse effects on the respiratory system. DOI: http://dx.doi.org/10.3126/hren.v10i3.7139 Health Renaissance; September-December 2012; Vol 10 (No.3);220-223